Research priorities in pancreatic surgery - Holze, Magdalena; Zlatopolskaia, Anna; Pianka, Frank; Pausch, Thomas; Diener, Markus K.; Antony, Pia-Anita; Loos, Martin; Michalski, Christoph; Klotz, Rosa; Probst, Pascal (BJS open, 2024)
Though magnificent technical and perioperative improvements have been made in the past decade, research in the field of pancreatic surgery continuously offers multiple opportunities for further approaches to reduce mortality and minimize the risk of potentially life-threatening complications. This is evident in the increasing quantity and improving quality of published randomized clinical trials (RCTs) on this topic1. Over the past decade, there has been an almost three-fold rise in the number of new publications per year dedicated to this topic, leading to a massive increase in available information and new data. As there are still evidence gaps that need to be addressed in pancreatic surgery research, the International Study Group of Pancreatic Surgery (ISGPS) developed the Evidence Map of Pancreatic Surgery (www.EVIglance.com) to provide a high-quality and readily accessible overview of the current evidence with regard to all aspects of pancreatic surgery and moreover to uncover the existing research gaps2.
Gesehen am 05.03.2025